Aza-Morita–Baylis–Hillman Reaction with Vinyl-oxadiazoles: An Expeditious Approach to Access New Heterocyclic Arrangements - Capretz-Agy, André; Fernandes, Fábio S.; Rodrigues, Manoel T., Jr.; Conti, Caroline; Coelho, Fernando (Synlett, 2020)
In this communication, we disclosed a new aza-MBH reaction in which traditional nucleophilic partners of these reactions (e.g., acrylates, nitroolefins or enones) were replaced by vinyl-1,2,4-oxadiazoles. Thus, the aza-MBH reaction between 5-aryl-3-vinyl-1,2,4-oxadiazoles and N-sulfonylimines, catalyzed by the mixture DABCO/AcOH, provides a class of new adduct in yields varying from 31% up to 93% in reaction times from 30 minutes to 24 hours. Due to the biological activities and technological applications associated with the 1,2,4-oxadiazole motifs, this new class of heterocycles offers great synthetic and commercial potentiality.
Keywords: vinyl-oxadiazoles; heterocycles; organocatalysis; Morita–Baylis–Hillman reaction; aza-Morita–Baylis–Hillman; nucleophilic partner